"A Fountainhead of Pure Musical Americana": Hobo Philosophy in Harry Partch's Bitter Music. Issue 4 (20th October 2017) - RAULERSON, GRAHAM
Abstract: Largely because of its troubled publication history, Bitter Music —Harry Partch's journal of a portion of his travels as a hobo—has attracted little scholarly or popular attention. This article aims to help elucidate Bitter Music by examining the influence of hobo philosophy on its creation and reception. Certain aspects of the historical and current hobo subculture's ideology—particularly bricolage, anarcho-syndicalism, radical egalitarianism, and non-hierarchical temporal perception—appear to motivate various factors in Partch's creation of the journal and his later attempts to destroy it. Additionally, I examine how hobo philosophy animates Partch's approach to speech, song, and instrumental music, culminating in a close reading of the journal's longest musical-textual entry. The article concludes with an examination of how Bitter Music 's publication history further enhances the resonance of hobo philosophy with the ways in which the journal is apprehended by readers and, in the current century, listeners.